Effects of combined usage of GGBS and fly ash on workability and mechanical properties of alkali activated geopolymer concrete with recycled aggregate. (1st May 2019) - Xie, Jianhe; Wang, Junjie; Rao, Rui; Wang, Chonghao; Fang, Chi
Abstract: Geopolymer binder and recycled aggregates are considered as the two important sustainable ingredients in concrete production. Ground granulated blast furnace slag (GGBS) and fly ash combination based geopolymeric recycled aggregates concretes (GRAC) were prepared as a substitution of normal concrete in order to reduce the consumption of ordinary Portland cement and natural aggregates as well as to make use of demolished waste concrete. The aim of this study is to investigate the combined effects of GGBS and fly ash considering water-binder (W/B) ratio on the fresh and hardened properties of alkali activated GRAC. The slump, setting time, compressive strength, stress-strain relation, elastic modulus, Poisson's ratio, toughness and failure mode of alkali activated GGBS and fly ash based GRAC containing 100% recycled coarse aggregates were experimentally examined. In addition, the hydration mechanisms were studied by XRD and SEM. Finally, the failure mechanism of this kind of novel green concrete subjected to compression was revealed. The results show that GGBS and fly ash exhibits a superior synergetic effect on the performance of GRAC, i.e. fly ash and GGBS are mainly responsible for the workability and mechanical properties, respectively. GGBS/fly ash ratio has a significant influence on the fresh and hardened properties of GRAC. Moreover, the effect of W/B ratio on GRAC strongly depends on the GGBS/fly ash ratio. GGBS content at less than 25% was found to slightly influence the consistency and compressive strength of GRAC. The combination of 50% GGBS and 50% fly ash with a 0.5 W/B ratio could provide excellent mechanical performance and workability for GRAC.